2017
DOI: 10.1159/000481881
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Alopecia Areata: A Retrospective Cohort Study

Abstract: Background: Alopecia areata is an immune-mediated disease presenting with sudden onset of nonscarring hair loss. Onset is more common earlier in life, and little is known regarding late-onset alopecia areata. Objectives: To describe the epidemiology, clinical patterns, disease course, and outcome of late-onset alopecia areata in Israeli patients referred to a tertiary medical center. Materials and Methods: This retrospective cohort study considered patients whose disease onset occurred at age ≥50 years. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 22 publications
5
13
0
11
Order By: Relevance
“…In contrast to this and in agreement with our recent study, all patient subgroups showed considerably higher prevalence of a family history of AA . The prevalence of a family history of atopy significantly decreased with age, while the prevalence of thyroid disorders increased with age; this is in agreement with the reported literature …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast to this and in agreement with our recent study, all patient subgroups showed considerably higher prevalence of a family history of AA . The prevalence of a family history of atopy significantly decreased with age, while the prevalence of thyroid disorders increased with age; this is in agreement with the reported literature …”
Section: Discussionsupporting
confidence: 93%
“…Several previous studies have demonstrated no association of late‐onset AA with atopy and thyroid disorders. However, similar to the present findings, a recent study conducted by us found such an association; this could be attributed to the differences in the definition of atopy and/or geographical differences …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of note, a late age of AA onset (> 50 years) is a major confounding variable associated with a significantly reduced prevalence of AA and atopy [17, 18, 20, 21]. For example, one cross-sectional study of Taiwanese late-onset AA patients ( n = 73) reported no association with currently active disease or personal or family history of atopy [18], while another Israeli study ( n = 29) reported a prevalence of atopy in 6.90% of late-onset AA patients [17], Interestingly, juvenile AA (< 16 years) may be associated with a more severe disease course than that of patients with disease onset after 16 years of age [16].…”
Section: Resultsmentioning
confidence: 99%
“…Late-onset AA is characterized by a marked female predominance, and disease severity is inversely proportional to age [17, 18], which is supported by the clinical consensus that young patients are often afflicted with a rapid disease progression, more extensive involvement, and a worse prognosis [53]. The association between AA and atopy among the pediatric population is controversial considering that an early disease onset often signifies a worse prognosis, while an increased age of onset is associated with a more mild disease course [16].…”
Section: Discussionmentioning
confidence: 99%